Efficacy and safety of biological and targeted-synthetic DMARDs: a systematic literature review informing the 2016 update of the ASAS/EULAR recommendations for the management of axial spondyloarthritis. Issue 1 (27th January 2017) - Sepriano, Alexandre; Regel, Andrea; van der Heijde, Désirée; Braun, Jürgen; Baraliakos, Xenofon; Landewé, Robert; Van den Bosch, Filip; Falzon, Louise; Ramiro, Sofia
Abstract : Objectives: To update the evidence for the efficacy and safety of (b)biological and (ts)targeted-synthetic disease-modifying anti-rheumatic drugs (DMARDs) in patients with axial spondyloarthritis (axSpA) to inform the 2016 update of the Assessment of SpondyloArthritis international Society/European League Against Rheumatism (ASAS/EULAR) recommendations for the management of axSpA. Methods: Systematic literature review (2009–2016) for randomised controlled trials (RCT), including long-term extensions, strategy trials and observational studies (the latter was only for safety assessment and a comparator was required). Interventions were any bDMARD or tsDMARD. All relevant efficacy and safety outcomes were included. Results: 76 papers and 24 abstracts fulfilled the inclusion criteria. Large treatment effects were found both in radiographic axSpA (r-axSpA) and non-radiographic axSpA (nr-axSpA) for all tumour necrosis factor inhibitors (TNFi) (NNT to achieve ASAS40 response ranged between 2.6–5.2 for r-axSpA and 2.3–5.4 for nr-axSpA). For nr-axSpA, efficacy was superior for those who had objective signs of inflammation (positive C reactive protein or inflammation on MRI-SI). Secukinumab 150 mg has shown efficacy in two phase 3 RCTs (NNT to achieve ASAS40 response: 3.4 and 4.0). Ustekinumab and tofacitinib have shown positive results in phase 2/proof-of-concept trials; trials with apremilast, rituximab, interleukin (IL)-6 antagonists and abatacept have failed their primary end points. New (unknown) safety signals were not found in the trials but long-term observational safety data for TNFi are still scarce. Conclusions: New evidence supports the efficacy and safety of TNFi both in r-axSpA and nr-axSpA. Secukinumab is the first drug targeting the IL-17 pathway in r-axSpA that has shown efficacy.